Inﬂuence of thickness reduction in base plate on elastic stress state of patch plate joint by combination of welding and bonding. Issue 1 (4th March 2019) - Hirohata, Mikihito; Fujimura, Naoki
ABSTRACT: For investigating the inﬂuence of thickness reduction in base plate on elastic stress state of patch plate joint by combination of welding and bonding, a series of experiment and analysis were conducted. A static tensile loading experiment was carried out. The thickness reductions of 2.5 mm were applied to both top and bottom surfaces of a base plate with a thickness of 12 mm. The thickness-reduced parts of the base plate were covered by the patch plates with a thickness of 6 mm. The joining methods of patch plates were only ﬁllet welding, only bonding and the combination of welding and bonding. The load-carrying eﬀect at the centre of the joint was improved by the combination of welding and bonding compared to the case with only welding. However, the stress reduction eﬀect around the welded part could not be clearly conﬁrmed from the experimental result. The 2D elastic analysis was performed for simulating the experiment and examining the stress reduction eﬀect around the welded part in detail. Furthermore, the inﬂuence of the degree of thickness reduction in base plate on the stress state around the welded part was investigated. The results indicated that the stress reduction eﬀect by the combination of welding and bonding was larger around the weld root rather than the weld toe.